Significance of miR-15a-5p and CNKSR3 as Novel Prognostic Biomarkers in Non-Small Cell Lung Cancer - Ergun, Sercan; Güney, Serkan; Temiz, Ebru; Petrovic, Nina; Gunes, Sezgin (Anti-Cancer Agents in Medicinal Chemistry, 2018)
Background: In recent years, targeted cancer treatment methods at various molecular levels have been developed for Non-Small Cell Lung Cancer (NSCLC), one of two major subtypes of lung cancer. miRNAbased clinical trials are currently the preferred targeted therapeutic strategy. Also, ceRNAs (competing endogenous RNA) would be the newest and the most effective approach to uncover novel interactions between mRNAs and miRNAs in NSCLC carcinogenesis. There are many factors influencing the efficiency of a miRNA to suppress or silence translation of the target mRNA. The most effective event is the presence of other RNAs showing ceRNA activity. These RNAs contain binding sites for specific miRNAs and enable miRNAs to bind these pseudo targets, instead of the original binding sites on the target mRNA. Therefore, the mRNA of the target gene is less affected by this miRNA, while the amount of miRNA remains the same in the media. Method: For this project, we determined that five clinically important different oncogenes (PDL1, FGFR1, DDX3X, SLC1A5, FXR1 ) are involved in the pathogenesis of NSCLC. For this purpose, we transfected model NSCLC cell line, A549, with miRNAs (miR-150-5p, miR-15a-5p, miR-503-5p) targeting these oncogenes to investigate whether these oncogenes will be suppressed at the mRNA level and also how the suppression efficiency of these miRNA on the oncogenes will be affected by possible ceRNA (CNKSR3, POU2F1, HIPK2) activities. Results: miR-15a-5p was determined to have the most suppressive effect on the five genes and three potential ceRNAs (p<0.05). Furthermore, CNKSR3 was the ceRNA most affected by all three miRNAs (p<0.05). Conclusion: CNKSR3 was affected more than the oncogenes known to act on NSCLC and this might make it a stronger and novel marker for use in possible treatment regimens designed using miR-15a-5p silencing effect on oncogenes in NSCLC pathogenesis. According to the literature, this is the first study associating NSCLC with miR-15a-5p and CNKSR3.
Keywords: CNKSR3